2004
DOI: 10.1038/sj.eye.6701368
|View full text |Cite
|
Sign up to set email alerts
|

Pars plana vitrectomy for traumatic cyclodialysis with persistent hypotony

Abstract: Figure 2 Closure of nasal cyclodialysis cleft is observed.Correspondence

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
(14 reference statements)
0
4
0
Order By: Relevance
“… 9 11 Meanwhile, Ishida et al reported a case treated by vitrectomy, cyclopexy with transscleral diathermy, and gas tamponade. 12 Medeiros et al 13 introduced the surgical method of vitrectomy, silicone oil, or gas endotamponade. A recent research studied large cyclodialysis clefts treated by multiple surgical steps, including vitrectomy, cryotherapy, phacoemulsification with placement of a capsular tension ring, and gas tamponade.…”
Section: Discussionmentioning
confidence: 99%
“… 9 11 Meanwhile, Ishida et al reported a case treated by vitrectomy, cyclopexy with transscleral diathermy, and gas tamponade. 12 Medeiros et al 13 introduced the surgical method of vitrectomy, silicone oil, or gas endotamponade. A recent research studied large cyclodialysis clefts treated by multiple surgical steps, including vitrectomy, cryotherapy, phacoemulsification with placement of a capsular tension ring, and gas tamponade.…”
Section: Discussionmentioning
confidence: 99%
“…As described above, the current surgical treatments for cyclodialysis include ciliary body suturing [1][2][3], cyclocryotherapy [4][5][6]22], laser photocoagulation [7][8][9][10], encircling [11,12], IOL suture fixation [13][14][15][16], and vitreous surgery [17][18][19][20][21]. Cyclocryotherapy and laser photocoagulation are performed to close the cyclodialysis cleft via the creation of an adhesion between the ciliary body and the sclera.…”
Section: Discussionmentioning
confidence: 99%
“…e encircling buckle is useful, especially for the cases with a wide area of angle recession and cyclodialysis [14]. For these cases with an extensive detachment of ciliary body, the multiple ciliary sutures which are challenging with a risk of complications such as intraocular hemorrhage and creating another cyclodialysis cleft [15] are required if the direct cyclopexy is attempted. e less invasive treatments, such as laser and cryotherapy, are usually not effective for these cases with a wide recession.…”
Section: Discussionmentioning
confidence: 99%